“La rehabilitación social según el COIP en la población carcelaria del centro de privación de libertad de personas adultas en conflicto con la ley” - Samaniego Jácome, Fabián Eduardo (2017)
The Ecuadorian State across the system of social rehabilitation seeks to re-insert to the social life of the individuals who have been deprived of the freedom, this program is dedicated for the accurate rehabilitation and development of the person evicted from the freedom to the social way, with the only end of going bringing them over to the way in the one that was unrolled before entering to fulfill a custodial sentence, this rehabilitation is given by means of a work supported during the whole process in the one that last a sorrow whom they have been condemned, establishing a specialized formation inside the area in the one that they are imprisoned. The system of Social Rehabilitation is fully established about the penitentiary regime with clear policies of treatment, but it is not fulfilled fully since at present one does not find due classified the Centers of Libertad's Privation inside the Country; this is there do not differ which are the centers of rehabilitation of high median or maximum safety; For such a reason, a suitable social rehabilitation does not exist to exceptions of few provinces in which it exists the centers of rehabilitation of maximum safety, inside other centers of national rehabilitation there are prisons overcrowding, which has provoked accumulation, due to the inadequate and former infrastructure preventing hereby one from giving a tidy used of the processes both in education and in labor methods. The social rehabilitation across the work has turned into a fundamental part of the change. creating in this way a right and a duty of the border with positive incident in his labor formation; in addition, every prison establishment should rely on professionals and personnel qualified that they should take forward the penitentiary consistent treatment in approaching the boarder in interdisciplinary form, in order to know it in all his aspects, having in it counts always his individuality at the moment of guiding it in the way of the reincorporation to the company, with the aim that they modify his future attitude opposite to the social way, trying to revert the conducts that separated it from the same one, nevertheless it is necessary to make notice that a professionals' deficit exists qualified to take adequately the above mentioned process of treatment. It is necessary to mention that the State has to invest much more in the correct change of infrastructures. machinery: and, hired a qualified personnel: for the correct rehabilitation of the person deprived of the freedom; which was helping in positive form for the rehabilitation to the company of the peopledeprived of the freedom.